Renal tubular impairment in children with idiopathic hypercalciuria - Skálová, Sylva; Kutílek, Stepán (Acta medica (Hradec Kralove), 2006)
Idiopathic hypercalciuria (IH) is defined as hypercalciuria that persists after correction of dietary inbalances and has no detectable cause. The excretion of urinary N-acetyl-beta-D-glucosaminidase (U-NAG), a marker of proximal tubular damage, has been previously reported as either increased or normal in children with IH. We evaluated U-NAG in 20 children (13 boys and 7 girls, mean age 10.3 years +/- 5.7 SD) with IH (urinary calcium excretion above 0.1 mmol/kg/24 hours, with no detectable cause) and with otherwise normal renal function tests. Ultrasound examination revealed urolithiasis (n=4) and nephrocalcinosis (n=1). The U-NAG values were evaluated in the spot urine collected from the second morning void and calculated as the urinary NAG/creatinine ratio (U-NAG/Cr) and expressed in nkat/mmol. The 24-hour urinary calcium excretion (U-Ca/24h) was assessed in a urinary sample from 24-hour collected urine and calculated in mmol/kg. The obtained results of U-Ca/24h and U-NAG/Cr were expressed as Z-scores. When compared to the reference data, the U-Ca/24h and U-NAG/Cr were significantly higher (p = 0.0004 and p = 0.006, respectively). There was no correlation between the U-NAG/Cr and U-Ca/24h (r = 0.18, p = 0.20). The U-NAG/Cr values were significantly higher in the 5 patients with urolithiasis/nephrocalcinosis, whether compared to the rest of the group (p = 0.02), or to the reference data (p = 0.01). The U-NAG/Cr activity was higher in 15 children without urolithiasis/nephrocalcinosis when compared to reference data (p < 0.01). There was no difference in U-Ca/24h between the children with and without urolithiasis/nephrocalcinosis (p = 0.58). These findings suggest that tubular impairment, as reflected by U-NAG/Cr, might occur in children with IH, especially in patients with urolithiasis/nephrocalcinosis. There doesn't seem to be a direct relationship between the U-NAG/Cr activity and the degree of calcium leakage.
Keywords: Child; Calcium; Urinary Calculi; močové kameny; vápník; Female; Kidney Tubules; Humans; ženské pohlaví; acetylglukosaminidasa; ledvinové kanálky; lidé; mužské pohlaví; nefrokalcinóza; Acetylglucosaminidase; Male; dítě; Nephrocalcinosis